The Effect of Total Asset Turnover (TATO) and Debt to Asset Ratio (DAR) on Return on Assets (ROA) in Companies in the Non-Primary Consumer Goods Retail Trading Sub-Sector on the Indonesia Stock Exchange for the 2021-2024 Period - Salsa Fauzia; NR. Ayke Nuraliati; Ayi Astuti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of Total Asset Turnover (TATO) and Debt to Asset Ratio (DAR) on Return on Assets (ROA) in non-primary consumer goods retail trade sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The background of this study is the fluctuation of profitability in the sub-sector amidst post-pandemic economic recovery and changes in consumption patterns. The method used is descriptive and verification with a quantitative approach, using secondary data from annual financial reports. The study population includes 109 financial reports from 32 companies, while the sample was selected by purposive sampling, resulting in 56 financial reports from 14 companies that meet the criteria. The data analysis technique uses panel data regression with three estimation models: Common Effect, Fixed Effect, and Random Effect, selected through the Chow test, Hausman test, and Lagrange Multiplier test. Classical assumption tests were conducted including multicollinearity and heteroscedasticity tests, as well as partial hypothesis testing (t-test) using the EViews 12 program. The results of the analysis showed that TATO partially had a positive and significant effect on ROA at a 5% significance level, while DAR had no effect on ROA. This finding indicates that a company's ability to optimize assets to generate sales plays an important role in increasing profitability, while the debt financing structure is not a direct determinant of the profit generated from assets. This study provides empirical contributions for company management and investors in evaluating factors that influence profitability in the non-primary consumer goods retail sub-sector.